The enhancement of the concept of liveability and inclusive community in relation to sustainable development - Irma Wani Othman; Azmin Pullong; Ismail Maidin (Global Academic Excellence, 2022)
The primary focus of this paper's discussion is the enhancement of the concept of liveability (KDH) in relation to development of a country in terms of economic growth, and the environment. This paper addresses liveability concept (KDH) as one of the crucial elements in the formation of Inclusive Communities (KI). It relates to the development of a country with a quality and good atmosphere, as well as unity amongst communities, in order to ensure the community's well-being in a country. Among the issues debated are (i) the transformation of rural development in developing and building competitive rural communities on par with urban communities, (ii) the formation of inclusive and liveable communities, (iii) the realisation of the national liveability index, and (iv) well-being & sustainability of life. This paper uses secondary sources, such as study results published in journals, scholarly literature, internet news sources, and public forums, to employ a qualitative methodology. According to the findings of the study, the measures employed by a country to measure its liveability, such as the liveability index, have a significant role in ensuring the health and sustainability of communal life. The focus of the future study is on the importance of a country's agenda being sensitive to the balance between developing and increasingly developed nations. This is consistent with the issues, difficulties, and strategies of a country undergoing a phase or process of implementing the liveability index framework.